Penerapan Alur Merdeka untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Putri, Weli Awalia; Kusmawati, Kusmawati (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This research aims to improve physics learning outcomes for class XI SMA Negeri 1 Bulukumba through implementing the independent flow. This type of research is Collaborative Classroom Action Research (PTK). The research method used is PTK from C. Kemmis and Mc. Taggart which consists of three stages, namely action planning, action implementation and observation, and reflection. The subjects in this research were students in class XI.3 of SMA Negeri 1 Bulukumba for the 2023/2024 academic year with a total of 35 students. The data collection instrument used in this research was a physics learning outcomes test which was analyzed using descriptive statistics. This research was carried out in two cycles. The results of this research show that the average learning outcome to cycle I was 78 and in cycle II it increased to 85. Classical completeness increased in cycle I by 66% and in cycle II by 89%. This shows that the percentage of student learning outcomes has increased each cycle. Based on this research, it can be concluded that the application of independent flow can improve the physics learning outcomes of students. Keywords: Independent Flow, Physics, Learning Outcomes